IMPLEMENTASI MODEL PEMBELAJARAN “WISATA LOKAL” UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR MATA PELAJARAN PERBAIKAN MOTOR OTOMOTIF DI KELAS XII TEKNIK KENDARAAN RINGAN SMK MUHAMMADIYAH PAKEM TAHUN PELAJARAN 2017/2018 - Adhi Catur Prabowo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Learning model "Local Tour" is a model that closer learners with the local environment or local potential. By applying the model of Local Tourism learning in SMK Muhammadiyah Pakem is expected to increase students' enthusiasm or interest in learning subjects Motor Repair Automotive (PMO) kususnya on diesel motor materials.Learning models Local Tour is very pleased and liked by students, in addition to not boring also the model of learning is also introduced to the students of the importance of preserving the tourist area didaerahnya which culminate with a sense of love for the culture of the nation or region sendiri. Apabila interest in learning students in SMK Muhammadiyah Pakem increased because of the application of Local Tourism learning model then automatically the learning results are also automatically increased.Keywords: Implementation, Local Tour, Interest and Results.